Implementation of Virtual Reality In Residential Interior Development Case Study: Bukit Baruga - Syarief Dienan Yahya; Fizar Syafaat; Muhammad Syafaat (Program Studi Teknik Komputer, 2024)
The implementation of Virtual Reality (VR) in housing interior development is the focus of this research, with a case study conducted in the residential area of